2016
DOI: 10.1186/s12962-016-0056-1
|View full text |Cite
|
Sign up to set email alerts
|

Cost-utility of ranibizumab versus aflibercept for treating Greek patients with visual impairment due to diabetic macular edema

Abstract: BackgroundTo conduct a cost-utility analysis of ranibizumab versus aflibercept for the treatment of patients with visual impairment due to diabetic macular edema (DME) in the Greek setting.MethodsA Markov model was adapted to compare the use of ranibizumab 0.5 mg (pro re nata-PRN and treat and extend-T&E) to aflibercept 2 mg (every 8 weeks after five initial doses) in DME. Patients transitioned at a 3-month cycle among nine specified health states (including death) over a lifetime horizon. Transition probabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…The analysis demonstrated that in a clinical setting characterised by the potential administration of all the three options licensed for the treatment of DME currently available, it emerged that: (i) treating a larger proportion of eligible patients with Dexamethasone implant would significantly reduce the healthcare expenditure, and/or free up resources to treat more patients; (ii) the preferable scenario for the regional healthcare service is that which supports patient access to a broad range of alternative technologies as first-choice treatment, which also coincides with maximising clinician choice; (iii) from the comparison between real life and clinical trial retreatment rates, a significant initial investment (within the 12-24 month-time window) would be required, even if could be amply rewarded in the long run (reporting on average the highest value of cost saving in the third year); (iv) the additional investments required to guarantee the retreatment rates used in the clinical trials could be mitigated by applying a higher market share of Dexamethasone, and (v) the inclusion of Aflibercept, both in second-line and in first-line treatment, resulted in a minimal economic impact for the healthcare service. The results of the presented economic analysis undertaken in the Italian setting are consistent with those published in the other European Countries (UK and Greece), from a healthcare decision maker's perspective, for the treatment of patients with DME (Regnier et al 2015;Kourlaba et al 2016;Romero-Aroca et al 2016). The economic savings resulting from the adoption of Dexamethasone could be reinvested within the same therapeutic area, thus (i) improving patient access and adherence to therapy, (ii) treating a wider population and (iii) reducing waiting lists.…”
Section: Discussionsupporting
confidence: 78%
“…The analysis demonstrated that in a clinical setting characterised by the potential administration of all the three options licensed for the treatment of DME currently available, it emerged that: (i) treating a larger proportion of eligible patients with Dexamethasone implant would significantly reduce the healthcare expenditure, and/or free up resources to treat more patients; (ii) the preferable scenario for the regional healthcare service is that which supports patient access to a broad range of alternative technologies as first-choice treatment, which also coincides with maximising clinician choice; (iii) from the comparison between real life and clinical trial retreatment rates, a significant initial investment (within the 12-24 month-time window) would be required, even if could be amply rewarded in the long run (reporting on average the highest value of cost saving in the third year); (iv) the additional investments required to guarantee the retreatment rates used in the clinical trials could be mitigated by applying a higher market share of Dexamethasone, and (v) the inclusion of Aflibercept, both in second-line and in first-line treatment, resulted in a minimal economic impact for the healthcare service. The results of the presented economic analysis undertaken in the Italian setting are consistent with those published in the other European Countries (UK and Greece), from a healthcare decision maker's perspective, for the treatment of patients with DME (Regnier et al 2015;Kourlaba et al 2016;Romero-Aroca et al 2016). The economic savings resulting from the adoption of Dexamethasone could be reinvested within the same therapeutic area, thus (i) improving patient access and adherence to therapy, (ii) treating a wider population and (iii) reducing waiting lists.…”
Section: Discussionsupporting
confidence: 78%
“…To the best of our knowledge, this is the first study to evaluate the 1-year healthcare expenditures for DME patients that are either Naive or Switch patients involving the drugs compared. Other studies have evaluated either cost-effectiveness of anti-VEGFs without dexamethasone or budget impact analysis with different scenarios (R egnier et al 2015;Kourlaba et al 2016;Ross et al 2016;Foglia et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In Greek patients with DME treated with anti-VEGF agents as monotherapy, our results demonstrate slightly higher QALYs + than QALYs -(difference + 0.03) for a mean follow-up of 1 year. Based on a previous study by Kourlaba et al in Greece, one would probably expect higher QALY gains in patients with DME, as the above authors found that total QALYs were 8.59 for ranibizumab T&E and 8.54 for a ibercept over a lifetime horizon [25]. However, the study by Kourlaba et al was conducted in the capital city of Athens, where availability and access to specialized medical services is more effective than in rural regions [39,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded, that during a 10-year time frame all interventions led to an increase in QALYs, and that ranibizumab was a cost-effective option compared to alternative therapies. [16] More recently, it was found that the use of a ibercept and ranibizumab in a hypothetical cohort of Greek patients with DME, led to an increase of 8.54 and 8.59 respectively in total QALYs over a lifetime horizon [25]. However, patients in this study were also assumed to attain similar baseline characteristics to the population included in the RESTORE trial [26].…”
Section: Introductionmentioning
confidence: 99%